The Eruption of the Mountain, -or- The Horrors of the 'Bocca del Inferno'. - (:unkn) unknown (Humphrey, H., 1794)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Volcanic eruption; Hell; Great Britain -- Politics and government -- 1760-1820